X-ray fluorescence determination method for glass fiber batch

The chemical components and COD content of glass fiber compound materials were detected by X-ray fluorescence spectrometer combined with tableting method, which solved the problem of detection lag and time-consuming in the prior art, achieved rapid and accurate detection, and improved the glass fiber pool kiln Stability of production.

CN119470519APending Publication Date: 2025-02-18JUSHI GRP CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411655548.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has problems such as lag, time-consuming, complicated process and susceptible to human error when detecting the chemical components and COD content of glass fiber compound materials, which affects the stability of glass fiber pool kiln production.

Method used

Using X-ray fluorescence spectrometer combined with tableting method, by preparing and calibrating samples, establishing working curves, making sample sheets and conducting detection, SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, SO3 in glass fiber compound Rapid detection of components such as B2O3, F, C.

Benefits of technology

It realizes rapid detection of 12 components of glass fiber compound materials, predicts the changes in the glass liquid components in advance, improves the stability of the glass fiber pool kiln wire drawing operation, reduces the pollution of chemical waste liquid, and saves manpower and material resources. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470519A_ABST
    Figure CN119470519A_ABST
Patent Text Reader

Abstract

The invention discloses an X-ray fluorescence determination method for a glass fiber batch. The method comprises the following steps: manufacturing a sample piece to be detected, preparing a calibration sample, manufacturing a calibration sample piece, establishing a working curve of an X-ray fluorescence spectrometer for detecting the glass fiber batch, analyzing the sample piece to be detected, and calculating the mass percent of a glass fiber component. According to the method, a wavelength dispersion X-ray fluorescence spectrometer is adopted for determining the chemical components such as fluorine, boron, sulfur, carbon, silicon and aluminum and the COD content in the glass fiber batch with different formulas, operation is easy and convenient, the analysis speed is high, the measurement accuracy and precision are good, pollution of chemical waste liquid is greatly reduced, and the method is suitable for industrial production. The components of the glass fiber and the sulfur and chemical oxygen demand (COD) in the glass fiber batch are predicted in advance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an X-ray fluorescence determination method for glass fiber batches, and in particular to a method for determining the chemical composition and COD content of glass fiber batches using an X-ray fluorescence spectrometer tablet pressing method. Background Art

[0002] Whether the glass fiber components are stable is the primary prerequisite for the normal production process of the glass fiber tank kiln. The accuracy of the glass fiber batch preparation directly determines the stability of the glass fiber components. In the production process of glass fiber batch, there may be incorrect formula adjustments, wrong raw materials, incorrect raw material detection, and weighing system failures. It usually takes 1 to 2 days for the glass fiber batch to be melted into glass in the tank kiln. There will be a lag in the detection of glass fiber components, which will seriously affect the normal production of glass fiber. In addition, the chemical oxygen demand (COD) and sulfur content of the glass fiber batch directly affect the melting effect of the tank kiln on the batch. Rapid and timely accurate detection of glass fiber batch components is of great significance to the production of glass fiber tank kilns.

[0003] Wavelength dispersive X-ray fluorescence spectrometer has been widely used in routine detection of geological, material, environmental and other samples. It is an important chemical analysis method today, with the advantages of simple sample preparation, fast analysis speed, high analysis precision and accuracy. According to the information published by the British Glass Society in 1975, X-ray fluorescence spectrometry has been applied to float glass detection. In recent years, there have been many reports on the detection of glass fiber components and related raw materials by related melts. However, the existing technology usually detects glass components, which will lag in actual control. In addition, the chemical analysis time is long, the process is complicated, and the test results are easily affected by human errors and reagents. Summary of the invention

[0004] The purpose of this application is to provide a detection method with simple operation, short time consumption, high detection efficiency and low environmental pollution, mainly for the detection of SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, SO3, B2O3, F, C and other components in glass fiber batches, which can predict the changes in glass components about two days in advance; and can detect sulfur and chemical oxygen demand (COD) at one time. This detection method can not only complete the rapid detection of 12 components in glass fiber batches, but also has good measurement accuracy and precision, greatly reducing the pollution of chemical waste liquid, and predicting the glass fiber components and sulfur and chemical oxygen demand (COD) in glass fiber batches in advance.

[0005] The present application provides a method for detecting the mass percentage of chemical components of a glass fiber batch, wherein the chemical substances in the glass fiber batch include SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, SO3, B2O3, F, and C. The detection method comprises the following steps:

[0006] 1S. Preparation of the sample to be tested: sampling during the conveying process of the glass fiber batch material, mixing evenly, grinding the batch material sample at a predetermined grinding frequency and grinding time, then adding a binder according to a predetermined ratio, continuing grinding, and taking out; using a tablet press to make a sample sheet under predetermined tablet pressing time and original force conditions;

[0007] 2S. Preparation of calibration samples: Select raw materials for making glass fiber batch, determine their values ​​respectively, and mix various raw materials according to the predetermined proportions to make a series of calibration samples;

[0008] 3S. Preparation of calibration sample: The calibration samples prepared in step 2S were mixed evenly, and the calibration sample was prepared by the method of step 1S;

[0009] 4S. Establishment of working curve for glass fiber batch detection by X-ray fluorescence spectrometer: Select the predetermined measurement conditions, use X-ray fluorescence spectrometer to scan the intensity of each calibration sample, and produce calibration curves for each element;

[0010] 5S. Analysis of the test sample: Using the calibration curve prepared in step 4S, the test sample prepared in step 1S is measured, and the corresponding calibration method is selected to obtain the mass percentage of each component in the glass fiber batch sample;

[0011] 6S. Calculation of the mass percentage of glass fiber batch components and COD content: Use the mass percentage of each component in the glass fiber batch sample obtained in step 5S, and then calculate the mass percentage of the glass fiber batch components and COD content based on the melting rate of the glass fiber formula.

[0012] Beneficial effects of this application:

[0013] The present application proposes a method for determining the mass percentage of chemical components of glass fiber batch using an X-ray fluorescence spectrometer. The above method can comprehensively solve the detection of SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, B2O3, SO3, F, and C components, predict the glass liquid components in advance, and control them in advance, which is of great significance to improving the stability of glass fiber pool kiln drawing operations; at the same time, it can realize the determination of SO3, F, and C components of glass fiber batch, filling the current technical gap.

[0014] The method of measuring the chemical composition of glass fiber batch material by X-ray fluorescence spectrometry in the present application has the following advantages compared with the existing technology:

[0015] First, the calibration samples prepared by the sample preparation method in the present application method have a square correlation coefficient of the standard line drawn on the X-ray fluorescence that is greater than 0.99, which overcomes the influence of the particle size and matrix effect of the sample piece on the X-ray fluorescence analysis, and successfully solves the detection problems of fluorine, sulfur and carbon; the samples are subjected to repeatability tests, and the relative standard deviations are less than 2%, which is suitable for daily analysis of components of glass fiber batches with different formulas, and has high analytical precision and accuracy.

[0016] Second, the method of this application has the characteristics of simple sample preparation, fast analysis speed, and simultaneous multi-element determination. Through practice, it has greatly shortened the determination time of glass fiber batch components. From receiving the sample to the relevant parties receiving the corresponding results, the entire time is controlled within 30 minutes.

[0017] Third, the application method can estimate the glass liquid components of the glass fiber tank kiln in advance, which is of great significance to the improvement of the stability of the glass fiber tank kiln drawing operation.

[0018] Fourth, in addition to the detection of constant components of glass fiber batch materials, the method of the present application can also calculate the COD content by detecting the C content, which not only greatly reduces the pollution of chemical waste liquid, but also saves manpower and material resources.

[0019] Fifth, the method of the present application also solves the problem of chemical detection of uniformity of glass fiber batch and total sulfur detection of glass fiber batch, which improves the detection efficiency and can also reduce the use of detection equipment such as carbon sulfur meters and reduce the use of conventional reagents.

[0020] Sixth, the method of the present application can measure the fluorine component in the glass fiber batch. According to the residual fluorine content in the glass fiber glass liquid, the fluorine emission in the tank kiln exhaust gas can be calculated, which has a positive significance for the input amount of exhaust gas treatment agents in the later stage. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] According to the following description of the drawings, the purpose, features and advantages of the specific implementation cases of the present application are described in detail, which will help those skilled in the art to better understand the practical significance of the present application.

[0022] Figure 1 is a schematic flow chart of an X-ray fluorescence determination method of a glass fiber batch according to the present application;

[0023] Figure 2 is a working curve diagram of the Kα line of Si according to an embodiment of the present application;

[0024] Figure 3is a Kα line working curve diagram of Al according to an embodiment of the present application;

[0025] Figure 4 is a working curve diagram of the Fe Kα line according to an embodiment of the present application;

[0026] Figure 5 is a Kα line working curve diagram of Ti according to an embodiment of the present application;

[0027] Figure 6 is a working curve diagram of the Kα line of Ca according to an embodiment of the present application;

[0028] Figure 7 is a working curve diagram of the Kα line of Mg according to an embodiment of the present application;

[0029] Figure 8 is a Kα line working curve diagram of K according to an embodiment of the present application;

[0030] Fig. 9 is a working curve diagram of the Kα line of Na according to an embodiment of the present application;

[0031] Fig.10 is a Kα line working curve diagram of S according to an embodiment of the present application;

[0032] Fig.11 is a Kα line working curve diagram of B according to an embodiment of the present application;

[0033] Fig.12 is a Kα line working curve diagram of F according to an embodiment of the present application;

[0034] Fig.13 4 is a working curve diagram of the Kα line of C according to an embodiment of the present application. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the specific embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other in the absence of conflict. The present application will be described in detail below in conjunction with the embodiments.

[0036] The present application provides a method for detecting the mass percentage of chemical components of a glass fiber batch, wherein the chemical substances in the glass fiber batch include SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, SO3, B2O3, F, and C. The detection method comprises the following steps:

[0037] 1S. Preparation of the sample to be tested: sampling during the conveying process of the glass fiber batch material, mixing evenly, grinding the batch material sample at a predetermined grinding frequency and grinding time, then adding a binder according to a predetermined ratio, continuing grinding, and taking out; using a tablet press to make a sample sheet under predetermined tablet pressing time and original force conditions;

[0038] 2S. Preparation of calibration samples: Select raw materials for making glass fiber batch, determine their values ​​respectively, and mix various raw materials according to the predetermined proportions to make a series of calibration samples;

[0039] 3S. Preparation of calibration sample: The calibration samples prepared in step 2S were mixed evenly, and the calibration sample was prepared by the method of step 1S;

[0040] 4S. Establishment of working curve for glass fiber batch detection by X-ray fluorescence spectrometer: Select the predetermined measurement conditions, use X-ray fluorescence spectrometer to scan the intensity of each calibration sample, and produce calibration curves for each element;

[0041] 5S. Analysis of the test sample: Using the calibration curve prepared in step 4S, the test sample prepared in step 1S is measured, and the corresponding calibration method is selected to obtain the mass percentage of each component in the glass fiber batch sample;

[0042] 6S. Calculation of the mass percentage of glass fiber batch components and COD content: Use the mass percentage of each component in the glass fiber batch sample obtained in step 5S, and then calculate the mass percentage of the glass fiber batch components and COD content based on the melting rate of the glass fiber formula.

[0043] Further, in step 1S, during the conveying process of the glass fiber batch material, samples are taken, and the same piece of material is taken 3 to 5 times, illustratively, 3 times, 4 times, and 5 times; 20 to 50g each time, illustratively, 50g, 40g, 30g, 20g, as long as it is in the range of 20 to 50g, and mixed evenly; then 20g to 50g of the batch material sample is taken and ground; illustratively, 30g, 40g, 50g, 20g, as long as it is in the range of 20 to 50g. The grinding frequency is controlled to 15-30Hz, and the grinding time is controlled to 30s to 90s; illustratively, the grinding frequency can be 25Hz, 20Hz, 15Hz, 30Hz, as long as it is controlled at 15 to 30Hz; the grinding time can be 40S, 50S, 60S, 70S, 80S, 90S, as long as it is in the range of 30 to 90S.

[0044] Furthermore, the binder is at least one of methyl cellulose, polyethylene, paraffin and starch, preferably methyl cellulose. The ratio of the binder to the sample is controlled to be 1:10-20; illustratively, it can be controlled to be 1:20, 1:18, 1:16, 1:14, 1:12, 1:10, as long as it is controlled within the range of 1:10-20.

[0045] Further, after adding the binder, the grinding time is continued for 10s to 30s, the pressure of the tablet press is controlled to be 10T to 40T, and the pressing time is controlled to be 10s to 30s. Exemplarily, the grinding time can be 20S, 30S, 10S, as long as it is controlled within the range of 10s to 30s, the pressure can be controlled to be 25T, 30T, 35T, 40T, as long as it is controlled within the range of 10 to 40T, and the pressing time can be controlled to be 20S, 25s, 30s, as long as it is controlled within the range of 10s to 30s.

[0046] Furthermore, the raw materials used to prepare the glass fiber batch in step 2S include quartz sand, pyrophyllite, kaolin, calcined limestone or limestone, calcined dolomite or magnesium powder, colemanite, fluorite, and sodium sulfate.

[0047] Furthermore, in step 2S, the chemical composition of the glass fiber batch calibration sample is selected and controlled within the following range, and the raw material components used in the glass fiber batch can be adjusted or the proportions of the raw materials during synthesis can be adjusted to adjust the component range to the required range.

[0048]

[0049] Furthermore, in step 5S, SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, and TiO2 are calibrated using a fixed empirical α coefficient (concentration); B2O3, F, and C are calibrated using a fixed empirical α coefficient mixed mode (concentration and intensity).

[0050] Furthermore, the fixed empirical α coefficient (concentration) calibration is calculated according to the following formula:

[0051] Ci=a+bI i ×(1+∑α ij C j )+P(I i )

[0052] In the formula, C i , C j : concentration of measured element and influencing element; a: intercept; b: slope; I i : X-ray fluorescence intensity of the element being measured; α ij : Fixed theoretical concentration α influence coefficient; P(I i ):Intercept supplement.

[0053] Furthermore, the fixed empirical α coefficient mixed mode (concentration and intensity) calibration method is calculated according to the following formula:

[0054] C i =a+bI i ×(1+∑α ij C j +∑β ik I k )+P(I i )

[0055] In the formula, C i , C j : concentration of measured element and influencing element; a: intercept; b: slope; I i : X-ray fluorescence intensity of the element being measured; α ij : Fixed theoretical concentration α influence coefficient; β ik : Fixed theoretical strength α influence coefficient; I k : affects the strength of the element; P(I i ):Intercept supplement.

[0056] Furthermore, after the sample is mixed with the binder and ground, the particle size of the ground sample is controlled to pass 48 μm, and the mass fraction of particles with a size of 1 μm to 40 μm is ≥ 95%.

[0057] Furthermore, in step 2S, the raw materials are calibrated, and the samples are dried at 100-110° C. for 1.5-2.5 hours; illustratively, the samples are dried at 105° C. for 2 hours, and after cooling, the X-ray fluorescence method or the corresponding national standards are used to detect and calibrate each element. The calibration results of each raw material are shown in Table 1 below.

[0058] Table 1 Results of the determination of each raw material

[0059] Raw material name <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[B2O3]]> C F Quartz sand 98.99 0.56 0.05 0.02 0.00 0.00 0.10 0.06 0.00 0.00 0.00 0.00 Pyrophyllite 70.99 19.93 0.37 0.35 0.00 0.00 0.27 0.07 0.16 0.00 1.12 0.00 Kaolin 46.07 37.44 0.90 1.41 0.05 0.07 0.60 0.08 0.01 0.00 0.81 0.00 Calcined limestone 0.61 0.40 0.13 0.00 92.29 0.59 0.00 0.00 0.00 0.00 1.12 0.00 limestone 0.26 0.01 0.04 0.00 55.66 0.08 0.00 0.00 0.00 0.00 11.00 0.00 Calcined Dolomite 1.17 0.19 0.14 0.00 53.09 28.44 0.00 0.00 0.00 0.00 4.10 0.00 Magnesium powder 12.13 0.50 0.34 0.00 1.86 65.06 0.00 0.00 0.05 0.00 3.40 0.00 boronite 5.55 0.16 0.05 0.02 26.87 2.44 0.00 0.20 0.35 39.79 0.00 0.00 fluorite 2.04 0.00 0.06 0.00 70.03 0.00 0.00 0.00 0.05 0.00 0.00 47.4 Sodium sulfate 0.00 0.00 0.00 0.00 0.00 0.00 0.00 43.23 55.77 0.00 0.00 0.00 soda ash 0.00 0.00 0.00 0.00 0.00 0.00 0.00 58.16 0.00 0.00 98.90 0.00

[0060] Among them, in the step 2S, the various raw materials are matched according to a predetermined ratio to make a series of calibration samples, specifically: no less than 20 calibration samples are prepared, and no less than 10 available points are available for each component (more than 10 when the standard sample of each element is used to make a standard line). Each raw material needs to be dried at 105°C for 2 hours and then cooled before use. Table 2 is the amount of each raw material required to melt each calibration sample into 1000g of glass liquid. According to the preparation of Table 2, the content of each calibration sample component in Table 3 is obtained.

[0061] Table 2 Required amount of each raw material to melt each calibration sample into 1000g glass liquid (g)

[0062]

[0063]

[0064] Table 3 Content of each calibration sample component

[0065]

[0066] Wherein, in the step 1S and the step 3S, after the test sample and the calibration sample are added with a binder and finally ground, the particle size is 48 μm, and the mass fraction of particles with a size of 1 μm to 40 μm is ≥95%.

[0067] Wherein, in the step 4S, the suitable measurement conditions are shown in Table 4.

[0068] Table 4 Optimal measurement conditions of X fluorescence for each component

[0069]

[0070]

[0071] Note: The above measurement conditions refer to Bruker S 8TIGER

[0072] Wherein, in step 4S, the calibration curve of each element is shown in Figure 2 to Figure 13 .

[0073] Among them, in the step 6S, the mass percentage of the glass fiber component is estimated, and the mass percentage of SiO2, Al2O3, Fe2O3, TiO2, CaO, MgO, K2O, Na2O, B2O3, SO3, and F in the glass fiber component are calculated according to the measurement results of the batch and the melting rate of the formula when the batch is sampled.

[0074] Wherein, in the step 6S, the COD content is the COD content obtained by dividing the measured component C content by 10 and then converting it into mg / kg.

[0075] The following is a specific example of the X-ray fluorescence determination method for glass fiber batch materials of the present application. The raw materials used in the examples are all materials currently used in production and are used after being determined in the laboratory, as shown in Table 1.

[0076] 1S. Preparation of the sample to be tested: Sampling is performed during the transportation of the glass fiber batch material. The same batch material is sampled 3 times, and about 50g is taken each time and mixed evenly; 30g of the batch material sample is ground in a grinder at a grinding frequency of 25Hz for 40s, 2g of a binder is added, and grinding is continued for 20s; about 8g of the sample is taken, and a 25T pressure is used on a tablet press for 20s to make a sample sheet;

[0077] 2S. Preparation of calibration samples: Select raw materials for glass fiber batch including quartz sand, pyrophyllite, kaolin, calcined limestone or limestone, calcined dolomite or magnesium powder, colemanite, fluorite, sodium sulfate raw materials, see the raw materials with fixed values ​​in Table 1, according to the ratio in Table 2, mix and prepare 21 calibration samples for standby;

[0078] 3S. Preparation of calibration sample tablets: Take about 50g of the batch sample of step 2S and mix them evenly; take 30g of the batch sample and grind it in a grinder at a grinding frequency of 25Hz for 40s, add 2g of binder, and continue grinding for 20s; take about 8g of the sample and use 25T pressure on a tablet press for 20s to prepare calibration sample tablets; the composition and content of the calibration sample are shown in Table 3;

[0079] 4S. Establish working curve: Use X-ray fluorescence spectrometer to scan the spectral lines of 21 calibration sample pieces prepared in step 3S, select the best analysis conditions, see Table 4, and measure the spectral line intensities of Si, Al, Fe, Ti, Ca, Mg, K, Na, S, B, F, and C in the calibration sample pieces respectively. The working curves of Si, Al, Fe, Ti, Ca, Mg, K, Na, S, B, F, and C are shown in Table 4. Figure 2-13 ,The results of measurement and analysis are shown in Tables 5 to 17;

[0080] Table 5 Statistics of SiO2 content measurement of calibration sample pieces

[0081]

[0082]

[0083] Table 6 Al2O3 content measurement statistics of calibration sample pieces

[0084] serial number Net Strength (kCPS) Chemical content (%) XRF content (%) Absolute deviation (%) Relative deviation (%) 1# 32.8030 13.9200 13.9190 -0.0010 -0.0092 2# 26.3170 9.5800 9.5780 -0.0020 -0.0180 3# 28.6730 11.1600 11.1550 -0.0050 -0.0450 4# 29.9480 12.0100 12.0080 -0.0020 -0.0150 5# 37.6040 17.1300 17.1320 0.0020 0.0089 6# 36.4940 16.3900 16.3890 -0.0010 -0.0078 7# 35.1570 15.4900 15.4940 0.0040 0.0260 8# 33.8320 14.6100 14.6070 -0.0030 -0.0180 9# 32.1920 13.5100 13.5100 0.0000 -0.0012 10# 31.7750 13.2300 13.2310 0.0010 0.0059 11# 31.1140 12.7900 12.7880 -0.0020 -0.0120 12# 30.4610 12.3500 12.3510 0.0010 0.0120 13# 29.7940 11.9100 11.9050 -0.0050 -0.0410 14# 29.1490 11.4700 11.4730 0.0030 0.0300 15# 28.7290 11.1900 11.1920 0.0020 0.0220 16# 27.8570 10.6100 10.6090 -0.0010 -0.0110 17# 27.6700 10.4800 10.4840 0.0040 0.0360 18# 27.2310 10.1900 10.1900 0.0000 -0.0005 19# 26.5950 9.7600 9.7640 0.0040 0.0450 20# 39.6010 18.4700 18.4680 -0.0020 -0.0110 21# 41.4750 19.7200 19.7220 0.0020 0.0100

[0085] Table 7 Fe2O3 content measurement statistics of calibration sample pieces

[0086]

[0087]

[0088] Table 8 Statistics of TiO2 content measurement of calibration sample pieces

[0089] serial number Net Strength (kCPS) Chemical content (%) XRF content (%) Absolute deviation (%) Relative deviation (%) 1# 19.9300 0.5210 0.5212 0.0002 0.0460 2# 14.0000 0.3550 0.3590 0.0040 1.1000 3# 16.1290 0.4140 0.4191 0.0051 1.2000 4# 17.2780 0.4470 0.4515 0.0045 1.0000 5# 24.2510 0.6420 0.6445 0.0025 0.3900 6# 23.2630 0.6140 0.6128 -0.0012 -0.2000 7# 22.0680 0.5810 0.5799 -0.0011 -0.1800 8# 20.8770 0.5470 0.5458 -0.0012 -0.2300 9# 19.4140 0.5060 0.5034 -0.0026 -0.5200 10# 19.0420 0.4960 0.4922 -0.0038 -0.7700 11# 18.4610 0.4800 0.4737 -0.0063 -1.3000 12# 17.8750 0.4630 0.4582 -0.0048 -1.0000 13# 17.2830 0.4470 0.4410 -0.0060 -1.3000 14# 16.7170 0.4310 0.4245 -0.0065 -1.5000 15# 16.3530 0.4210 0.4126 -0.0084 -2.0000 16# 8.0000 0.1860 0.1886 0.0026 1.4000 17# 7.9270 0.1840 0.1865 0.0025 1.4000 18# 7.7520 0.1790 0.1826 0.0036 2.0000 19# 7.4930 0.1720 0.1753 0.0033 1.9000 20# 26.0070 0.6910 0.6979 0.0069 1.0000 21# 27.6950 0.7390 0.7456 0.0066 0.8900

[0090] Table 9 CaO content measurement statistics of calibration sample pieces

[0091]

[0092]

[0093] Table 10 MgO content measurement statistics of calibration sample pieces

[0094] serial number Net Strength (kCPS) Chemical content (%) XRF content (%) Absolute deviation (%) Relative deviation (%) 1# 42.5300 4.7700 4.7700 0.0000 -0.0087 2# 109.3200 12.1900 12.1910 0.0010 0.0098 3# 103.9700 11.6000 11.5970 -0.0030 -0.0290 4# 99.6200 11.1100 11.1130 0.0030 0.0280 5# 96.7400 10.7900 10.7930 0.0030 0.0260 6# 92.6500 10.3400 10.3390 -0.0010 -0.0120 7# 88.7900 9.9100 9.9100 0.0000 -0.0023 8# 84.9300 9.4800 9.4810 0.0010 0.0080 9# 80.2100 8.9600 8.9570 -0.0030 -0.0360 10# 72.9600 8.1500 8.1510 0.0010 0.0087 11# 65.1200 7.2800 7.2800 0.0000 -0.0044 12# 57.3600 6.4200 6.4180 -0.0020 -0.0370 13# 51.8500 5.8100 5.8060 -0.0040 -0.0750 14# 43.6400 4.8900 4.8930 0.0030 0.0530 15# 36.4400 4.0900 4.0930 0.0030 0.0630 16# 28.6200 3.2200 3.2240 0.0040 0.1200 17# 21.2200 2.4000 2.4010 0.0010 0.0620 18# 13.2100 1.5100 1.5120 0.0020 0.1200 19# 11.0000 1.2700 1.2660 -0.0040 -0.3300 20# 7.6800 0.9000 0.8970 -0.0030 -0.3000 21# 4.5700 0.5500 0.5510 0.0010 0.2600

[0095] Table 11 K2O content measurement statistics of calibration sample pieces

[0096]

[0097]

[0098] Table 12 Statistics of Na2O content measurement of calibration sample pieces

[0099] serial number Net Strength (kCPS) Chemical content (%) XRF content (%) Absolute deviation (%) Relative deviation (%) 1# 2.6384 0.4980 0.4976 -0.0004 -0.0790 2# 1.1824 0.1370 0.1370 0.0000 0.0200 3# 1.4764 0.2100 0.2098 -0.0002 -0.0780 4# 1.8404 0.3000 0.3000 0.0000 -0.0060 5# 4.5774 0.9780 0.9778 -0.0002 -0.0200 6# 4.4374 0.9430 0.9431 0.0001 0.0140 7# 4.3074 0.9110 0.9109 -0.0001 -0.0070 8# 4.1704 0.8770 0.8770 0.0000 0.0010 9# 3.8934 0.8080 0.8084 0.0004 0.0510 10# 3.7574 0.7750 0.7747 -0.0003 -0.0350 11# 3.6244 0.7420 0.7418 -0.0002 -0.0280 12# 3.4924 0.7090 0.7091 0.0001 0.0140 13# 3.3584 0.6760 0.6759 -0.0001 -0.0120 14# 3.2654 0.6530 0.6529 -0.0001 -0.0180 15# 3.1294 0.6190 0.6192 0.0002 0.0330 16# 2.8644 0.5530 0.5536 0.0006 0.1000 17# 2.7854 0.5340 0.5340 0.0000 0.0022 18# 2.4774 0.4580 0.4577 -0.0003 -0.0580 19# 2.1404 0.3740 0.3743 0.0003 0.0740 20# 1.7924 0.2880 0.2881 0.0001 0.0330 21# 1.6464 0.2520 0.2519 -0.0001 -0.0250

[0100] Table 13 Statistics of SO3 content measurement of calibration sample pieces

[0101]

[0102]

[0103] Table 14 B2O3 content measurement statistics of calibration sample pieces

[0104] serial number Net Strength (kCPS) Chemical content (%) XRF content (%) Absolute deviation (%) Relative deviation (%) 1# 0.2815 2.7100 2.7150 0.0050 0.1900 2# 0.0000 0.0000 0.0000 0.0000 0.0000 3# 0.0000 0.0000 0.0000 0.0000 0.0000 4# 0.0000 0.0000 0.0000 0.0000 0.0000 5# 0.2115 1.6100 1.6040 -0.0060 -0.3700 6# 0.2505 2.2300 2.2230 -0.0070 -0.3100 7# 0.3075 3.1200 3.1277 0.0077 0.2500 8# 0.3355 3.5600 3.5722 0.0122 0.3400 9# 0.3905 4.4500 4.4452 -0.0048 -0.1100 10# 0.4185 4.8900 4.8896 -0.0004 -0.0084 11# 0.4465 5.3400 5.3340 -0.0060 -0.1100 12# 0.4745 5.7800 5.7785 -0.0015 -0.0270 13# 0.5025 6.2300 6.2229 -0.0071 -0.1100 14# 0.5375 6.7800 6.7784 -0.0016 -0.0230 15# 0.5665 7.2300 7.2387 0.0087 0.1200 16# 0.0000 0.0000 0.0000 0.0000 0.0000 17# 0.0000 0.0000 0.0000 0.0000 0.0000 18# 0.0000 0.0000 0.0000 0.0000 0.0000 19# 0.0000 0.0000 0.0000 0.0000 0.0000 20# 0.0000 0.0000 0.0000 0.0000 0.0000 21# 0.0000 0.0000 0.0000 0.0000 0.0000

[0105] Table 15 Statistics of F content measurement of calibration sample pieces

[0106]

[0107]

[0108] Table 16 C content measurement statistics of calibration sample pieces

[0109] serial number Net Strength (kCPS) Chemical content (%) XRF content (%) Absolute deviation (%) Relative deviation (%) 1# 0.3620 0.7210 0.7215 0.0005 0.0660 2# 0.6430 0.9890 0.9885 -0.0005 -0.0510 3# 0.6410 0.9860 0.9866 0.0006 0.0600 4# 0.6400 0.9850 0.9856 0.0006 0.0650 5# 0.5920 0.9410 0.9400 -0.0010 -0.1000 6# 0.5530 0.9030 0.9030 0.0000 -0.0034 7# 0.5310 0.8820 0.8821 0.0001 0.0073 8# 0.5040 0.8570 0.8564 -0.0006 -0.0690 9# 0.4610 0.8160 0.8155 -0.0005 -0.0560 10# 0.4290 0.7850 0.7851 0.0001 0.0180 11# 0.3810 0.7390 0.7395 0.0005 0.0710 12# 0.3490 0.7090 0.7091 0.0001 0.0170 13# 0.3190 0.6810 0.6806 -0.0004 -0.0570 14# 0.2610 0.6260 0.6255 -0.0005 -0.0800 15# 0.2100 0.5770 0.5770 0.0000 0.0061 16# 0.4640 0.8180 0.8184 0.0004 0.0490 17# 0.5930 0.9410 0.9410 0.0000 -0.0022 18# 0.5500 0.9000 0.9001 0.0001 0.0130 19# 0.3650 0.7240 0.7243 0.0003 0.0450 20# 0.3440 0.7050 0.7044 -0.0006 -0.0900 21# 0.3580 0.7170 0.7177 0.0007 0.0940

[0110] 5S. Analyze the sample to be tested: Under the same measurement conditions as in Table 4, measure the spectral line intensity of Si, Al, Fe, Ti, Ca, Mg, K, Na, S, B, F, and C in the sample to be analyzed obtained in step 1S, and measure the fluorescence intensity of the sample to be analyzed according to the working curve calibrated in step 4S to obtain the contents of SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, SO3, B2O3, F, and C in the sample to be analyzed, and convert C into COD content;

[0111] 6S. Calculation of mass percentage of glass fiber batch components and COD content: Sample 1 was selected and the above method was repeated for 12 times. The statistical results of the measurement results are shown in Table 17. It can be seen from Table 17 that the measurement method of the present application has good reproducibility.

[0112] Table 17 Calibration sample repeated measurement statistics

[0113]

[0114] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for X-ray fluorescence determination of glass fiber batch, wherein the chemical substances in the glass fiber batch components include SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, SO3, B2O3, F, and C, characterized in that: The following steps are involved: 1S. Preparation of the sample to be tested: sampling during the conveying process of the glass fiber batch material, mixing evenly, grinding the batch material sample at a predetermined grinding frequency and grinding time, then adding a binder according to a predetermined ratio, continuing grinding, and taking out; Using a tablet press to prepare a sample tablet under predetermined tableting time and original force conditions; 2S. Preparation of calibration samples: Select raw materials for making glass fiber batch, determine their values ​​respectively, and mix various raw materials according to the predetermined proportions to make a series of calibration samples; 3S. Preparation of calibration sample: The calibration samples prepared in step 2S were mixed evenly, and the calibration sample was prepared by the method in step 1S; 4S. Establishment of working curve for glass fiber batch detection by X-ray fluorescence spectrometer: Select the predetermined measurement conditions, use X-ray fluorescence spectrometer to scan the intensity of each calibration sample, and produce calibration curves for each element; 5S. Analysis of the sample to be tested: Using the calibration curve prepared in step 4S, the sample to be tested prepared in step 1S is measured, and the corresponding calibration method is selected to obtain the mass percentage of each component in the glass fiber batch sample; 6S. Calculation of the mass percentage of glass fiber batch components and COD content: Use the mass percentage of each component in the glass fiber batch sample obtained in step 5S, and then calculate the mass percentage of the glass fiber batch components and COD content based on the melting rate of the glass fiber formula.

2. The X-ray fluorescence determination method of glass fiber batch according to claim 1, characterized in that: In the step 1S, samples are taken during the conveying process of the glass fiber batch material, and the same piece of material is taken 3 to 5 times, 20 to 50 g each time, and mixed evenly; then 20 g to 50 g of the batch material sample is taken and ground; the grinding frequency is controlled to 15-30 Hz, and the grinding time is controlled to 30 s to 90 s.

3. The X-ray fluorescence determination method of glass fiber batch according to claim 1, characterized in that: The binder is at least one of methyl cellulose, polyethylene, paraffin and starch; the ratio of the binder to the sample is controlled to be 1:10-15.

4. The X-ray fluorescence determination method of glass fiber batch according to claim 1, characterized in that: In the step 1S, after the binder is added, the grinding time is continued for 10s to 30s, the pressure of the tablet press is controlled to be 10T to 40T, and the pressing time is controlled to be 10s to 30s.

5. The X-ray fluorescence determination method of glass fiber batch according to claim 1, characterized in that: The raw materials used to prepare the glass fiber compound in step 2S include quartz sand, pyrophyllite, kaolin, calcined limestone or limestone, calcined dolomite or magnesium powder, colemanite, fluorite, and sodium sulfate.

6. The X-ray fluorescence determination method of glass fiber batch according to claim 5, characterized in that: In step 2S, the chemical composition range of the glass fiber batch calibration sample is selected to be controlled as follows:

7. The X-ray fluorescence determination method of glass fiber batch according to claim 1, characterized in that: In step 5S, the SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, and TiO2 are calibrated using a fixed empirical α coefficient; and the B2O3, F, and C are calibrated in a mixed mode using a fixed empirical α coefficient.

8. The X-ray fluorescence determination method of glass fiber batch according to claim 7, characterized in that: The fixed empirical alpha coefficient calibration is calculated according to the following formula: C i =a+bI i ×(1+∑α ij C j )+P(I i ) In the formula, C i , C j : concentration of measured element and influencing element; a: intercept; b: slope; I i : X-ray fluorescence intensity of the element being measured; α ij : Fixed theoretical concentration α influence coefficient; P(I i ):Intercept supplement.

9. The X-ray fluorescence determination method of glass fiber batch according to claim 7, characterized in that: The fixed empirical alpha coefficient mixed mode calibration method is calculated according to the following formula: C i =a+bI i ×(1+∑α ij C j +∑β ik I k )+P(I i ) In the formula, C i , C j : concentration of measured element and influencing element; a: intercept; b: slope; I i : X-ray fluorescence intensity of the element being measured; α ij : Fixed theoretical concentration α influence coefficient; β ik : Fixed theoretical strength α influence coefficient; I k : affects the strength of the element; P(I i ):Intercept supplement.

10. The X-ray fluorescence determination method of glass fiber batch according to claim 3, characterized in that: After the sample is mixed with the binder and ground, the particle size of the ground sample is controlled to pass 48 μm, and the mass fraction of particles with a particle size of 1 μm to 40 μm is ≥95%.